THE INFLUENCE OF SERVICESCAPE AND SERVICE ENCOUNTER ON CONSUMER EMOTION, PERCEIVED SERVICE QUALITY, AND CONSUMER SATISFACTION - SUSANTO, FADLY FERDHIAN; SETYANTO, REFIUS PRADIPTA (INDONESIAN RESEARCH SOCIETY, 2018)
The emergence of the restaurant allows people to not have to cook for themselves. Inrestaurant, consumer enable to get some food and baverage to full fill their needs. Recently,many kind of restaurant that offer pleasant service include the interior decoration as well asthe exterior are attractive and also put forward the good service by relying on a qualitywaiter. This kind of service is called as service environment (servicescape and serviceencounter) where the restaurant offer pleasant servicescape and service encounter toinfluence positive consumer emotion for satisfying consumer for satisfying consumerbecause of the consumer perceived service quality will increase. This new way of pleasantservice environment has the potential for greater impact on consumer. Therefore, the aim ofthis research is to know the effect that servicescape and service encounter in restaurant onconsumers? emotion (pelasure and arousal), perceived service quality, and consumersatisfaction. The research methodology used for this study is a case study with surveyresearch method. Convenience sampling technique derived from non-probability samplingtechniques are used for sample selection. The sample of this research is 257, from peoplewho have visited Warunk Upnormal Purwokerto. Statistical software SPSS and AMOS isused to analyze the data. The findings in this area will help Warunk Upnormal Purwokertoand other marketers to reach out its potential customers and align their marketing effort inefficient way by pay attention on the marketing policies about Servicescape and serviceencounter. The limitations of the research is some respondents not read and answer thequestion clearly and made it not represent their exact perception